2016
DOI: 10.1107/s160057671601637x
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the limits of crystallography

Abstract: A very serious concern of scientists dealing with crystal structure refinement, including theoretical research, pertains to the characteristic bias in calculated versus measured diffraction intensities, observed particularly in the weak reflection regime. This bias is here attributed to corrective factors for phonons and, even more distinctly, phasons, and credible proof supporting this assumption is given. The lack of a consistent theory of phasons in quasicrystals significantly contributes to this characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 56 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…It can be shown that the coordinates in the statistical approach are related by strict rules to the perpendicularspace coordinates, providing a clear interpretation of the atomic surface (Wolny et al, 2002). This is true as long as the phonons are not part of the model and are excluded from the distribution (Wolny et al, 2016). In this article, we limit the discussion to phason effects, therefore the notion of the distribution in the AUC is fully equivalent to the notion of the atomic surface in the higher-dimensional approach.…”
Section: The Penrose Tilingmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be shown that the coordinates in the statistical approach are related by strict rules to the perpendicularspace coordinates, providing a clear interpretation of the atomic surface (Wolny et al, 2002). This is true as long as the phonons are not part of the model and are excluded from the distribution (Wolny et al, 2016). In this article, we limit the discussion to phason effects, therefore the notion of the distribution in the AUC is fully equivalent to the notion of the atomic surface in the higher-dimensional approach.…”
Section: The Penrose Tilingmentioning
confidence: 98%
“…The red prism represents the region corresponding to the distribution of the reference vertex O. The height of the prism is proportional to the flip probability (Wolny et al, 2016). Since the flip makes the O positions unoccupied and the node of the Penrose tiling is shifted to the O 0 positions, which previously were empty, part of the distribution in the AUC is cut out from the region of the O position and is shifted to the region corresponding to the O 0 node.…”
Section: Phason Flipmentioning
confidence: 99%
“…However, also other function types, like harmonic or flat, can be equally good. In [49] it was shown that the three listed function types used as generating functions of phonon disorder in model structures (including periodic ones) are reflected in change of P(u) distribution function. As already mentioned, the distribution is an object constructed in physical space, that is why easily maps all the changes of atomic arrangement, like structural disorder.…”
Section: Phononsmentioning
confidence: 99%
“…Harmonic or flat function G(u p ) leads to Bessel-or cardinal sine-function type of the corrective factor as a direct result of Fourier transforming. For details on the exact mathematical derivation see [49]. Phononic disorder influences strongly intensities of reflections in the diffraction pattern.…”
Section: Phononsmentioning
confidence: 99%
“…Also, the comparison with periodic crystals was discussed. For details see [19]. Here we focus on the Fibonacci chain and standard exponential D-W factor.…”
Section: Phononsmentioning
confidence: 99%